Medication use in European primary care patients with lower respiratory tract infection: an observational study. - Hamoen, M; Broekhuizen, B; Little, P; Melbye, H; Coenen, S; Goossens, H; Butler, C; Francis, N; Verheij, T (2014)
BACKGROUND It is largely unknown what medication is used by patients with lower respiratory tract infection (LRTI). AIM To describe the use of self-medication and prescribed medication in adults presenting with LRTI in different European countries, and to relate self-medication to patient characteristics. DESIGN AND SETTING An observational study in 16 primary care networks in 12 European countries. METHOD A total of 2530 adult patients presenting with LRTI in 12 European countries filled in a diary on any medication used before and after a primary care consultation. Patient characteristics related to self-medication were determined by univariable and multivariable logistic regression analysis. RESULTS The frequency and types of medication used differed greatly between European countries. Overall, 55.4% self-medicated before consultation, and 21.5% after consultation, most frequently with paracetamol, antitussives, and mucolytics. Females, non-smokers, and patients with more severe symptoms used more self-medication. Patients who were not prescribed medication during the consultation self-medicated more often afterwards. Self-medication with antibiotics was relatively rare. CONCLUSION A considerable amount of medication, often with no proven efficacy, was used by adults presenting with LRTI in primary care. There were large differences between European countries. These findings should help develop patient information resources, international guidelines, and international legislation concerning the availability of over-the-counter medication, and can also support interventions against unwarranted variations in care. In addition, further research on the effects of symptomatic medication is needed.